2016
DOI: 10.1037/apl0000055
|View full text |Cite
|
Sign up to set email alerts
|

The long road to employment: Incivility experienced by job seekers.

Abstract: This study addresses how job seekers' experiences of rude and discourteous treatment--incivility--can adversely affect self-regulatory processes underlying job searching. Using the social-cognitive model (Zimmerman, 2000), we integrate social-cognitive theory with the goal orientation literature to examine how job search self-efficacy mediates the relationship between incivility and job search behaviors and how individual differences in learning goal orientation and avoid-performance goal orientation moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 83 publications
1
38
0
Order By: Relevance
“…Furthermore, it has been observed that the fear of future unemployment is detrimental to the well‐being of young adults and might be a cause of stress in itself, particularly in countries with high unemployment rates (Knabe & Rätzel, ). Several studies found that youth unemployment can decrease physical and mental health (Ali, Ryan, Lyons, Ehrhart, & Wessel, ; Brown et al, ; Kozieł, Lopuszańska, Szklarska, & Lipowicz, ; Gallo et al, ; Sullivan & von Wachter, ; Roelfs, Shor, Davidson, & Schwartz, ; Urbanos‐Garrido & Lopez‐Valcarcel, ; Wanberg, ). Other studies have shown that the negative effects of youth unemployment on mental health can remain during adulthood, even without experiencing unemployment again (Fergusson, McLeod, & Horwood, ; Hammarström & Janlert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been observed that the fear of future unemployment is detrimental to the well‐being of young adults and might be a cause of stress in itself, particularly in countries with high unemployment rates (Knabe & Rätzel, ). Several studies found that youth unemployment can decrease physical and mental health (Ali, Ryan, Lyons, Ehrhart, & Wessel, ; Brown et al, ; Kozieł, Lopuszańska, Szklarska, & Lipowicz, ; Gallo et al, ; Sullivan & von Wachter, ; Roelfs, Shor, Davidson, & Schwartz, ; Urbanos‐Garrido & Lopez‐Valcarcel, ; Wanberg, ). Other studies have shown that the negative effects of youth unemployment on mental health can remain during adulthood, even without experiencing unemployment again (Fergusson, McLeod, & Horwood, ; Hammarström & Janlert, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al. () found that incivility interacted with AGO to predict job search self‐efficacy, but it did not interact with LGO. Correspondingly, we find that DA fit interacts with AGO but not LGO.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ali et al. () found that AGO moderated the effects of perceived incivility on job search self‐efficacy, which in turn related to search intensity. da Motta Veiga and Turban () found that the perceived stress–job search intensity relationship was stronger among those with stronger LGO.…”
Section: Study 1: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations